FAKTOR – FAKTOR YANG MEMPENGARUHI KUALITAS AUDIT: SKEPTISME DAN AUDIT TENURE - Sudiardjo, Ferryanto; Siregar, Anitaria; Ridaryanto, Petrus (BALANCE: Jurnal Akuntansi, Auditing dan Keuangan, 2024)
Financial statements are one of the main things that can make investors invest their capital in business, this is the basic reference for investors/investors to see if the company has good/bad quality. This study aims to analyze the influence of keptism and audit tenure on audit quality. The polulation of this research is an external auditor who is still actively working around the province of DKI Jakarta with the level of junior director, senior auditor, supervisor, manager, and partner. The sampling method used in this study is random sampling. And this study managed to collect 32 respondents. The data analysis methods used are descriptive statistical tests, data quality tests, classical assumption tests, and hypothesis tests using statistical for social science software version 26. The results of the hypothesis test show that skepticism influences audit quality, and tenure audit has no effect on audit quality.